Feeding practices and risk factors for chronic infant undernutrition among refugees and migrants along the Thailand-Myanmar border: a mixed-methods study - A. H. Hashmi (2020)
© 2019 The Author(s). Background: This study aims to provide a comprehensive understanding of maternal risk factors, infant risk factors and maternal infant feeding practices among refugees and migrants along the Thailand-Myanmar border. Methods: This study employed a mixed-methods approach with two components: (1) cross-sectional survey (n = 390) and (2) focus group discussions (n = 63). Participants were chosen from one of three clinics providing antenatal and delivery services for Karen and Burman refugees and migrants along the border. Participants were pregnant women and mother-infant dyads. Results: Refugee and migrant mothers demonstrated high rates of suboptimal breastfeeding and low rates of minimum dietary diversity and acceptable diet. Multivariable regression models showed infant stunting (AOR: 2.08, 95% CI: 1.12, 3.84, p = 0.020) and underweight (AOR: 2.26, 95% CI: 1.17, 4.36, p = 0.015) to have increased odds among migrants, while each 5 cm increase in maternal height had decreased odds of stunting (AOR: 0.50, 95% CI: 0.38, 0.66, p < 0.001) and underweight (AOR: 0.64, 95% CI: 0.48, 0.85, p = 0.002). In addition, small-for-gestational-age adjusted for length of gestation, infant age and gender increased odds of infant's stunting (AOR: 3.42, 95% CI: 1.88, 6.22, p < 0.001) and underweight (AOR: 4.44, 95% CI: 2.36, 8.34, p < 0.001). Using the Integrated Behavioural Model, focus group discussions explained the cross-sectional findings in characterising attitudes, perceived norms, and personal agency as they relate to maternal nutrition, infant malnutrition, and infant feeding practices. Conclusions: Inadequate infant feeding practices are widespread in refugee and migrant communities along the Thailand-Myanmar border. Risk factors particular to maternal nutrition and infant birth should be considered for future programming to reduce the burden of chronic malnutrition in infants.